RETRACTED: The Effect of Physical Work Environment, Work Discipline, and Financial Compensation on the Performance of Employees of the National Archives of the Republic of Indonesia - Rayhan Fernanda; Ahmad Cik; Kumba Digdowiseiso (Journal of Social Science)
This research is used to determine the presence or absence of a physical work environment, work discipline and financial compensation for the performance of employees of the National Archives of the Republic of Indonesia. By taking into account the level of control of human resources (HR), an agency is expected and makes a major contribution in improving employee performance. This view also uses primary data. The data collection technique used was to use questionnaires received by distributing questionnaires through google form to 104 employees of the National Archives. The information analysis approach used in this review is multiple linear regression evaluation, which is operated through the SPSS 23 application. Based on the results of this study shows that the variables of physical work environment, work discipline and financial compensation have a significant effect on employee performance. That partially physical work environment variables have a significant effect on employee performance. That the variable of work discipline has a dominant effect on employee performance. And the variable of financial compensation has a significant positive effect on the performance of employees of the National Archives of the Republic of Indonesia.